2006
DOI: 10.1152/jn.01077.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Influx, But Not Ca2+ Release From Internal Stores, Is Required for the PACAP-Induced Increase in Excitability in Guinea Pig Intracardiac Neurons

Abstract: Mechanisms modulating the pituitary adenylate cyclase activating polypeptide (PACAP)-induced increase in excitability have been studied using dissociated guinea pig intrinsic cardiac neurons and intact ganglion preparations. Measurements of intracellular calcium (Ca2+) with the fluorescent Ca2+ indicator dye fluo-3 indicated that neither PACAP nor vasoactive intestinal polypeptide (VIP) at either 100 nM or 1 microM produced a discernible elevation of intracellular Ca2+ in dissociated intracardiac neurons. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Experiments were performed on atrial whole mount preparations containing the intrinsic cardiac ganglia as described previously (Braas et al, 1998;Tompkins et al, 2006Tompkins et al, , 2007. Atrial whole mount preparations were dissected from the heart in ice-cold, standard Krebs' solution (121 mM NaCl, 5.9 mM KCl, 2.5 mM CaCl 2 , 1.2 mM MgCl 2 , 25 mM NaHCO 3 , 1.2 mM NaH 2 PO 4 , and 8 mM glucose), with the pH maintained at 7.4 by aeration with 95% O 2 , 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were performed on atrial whole mount preparations containing the intrinsic cardiac ganglia as described previously (Braas et al, 1998;Tompkins et al, 2006Tompkins et al, , 2007. Atrial whole mount preparations were dissected from the heart in ice-cold, standard Krebs' solution (121 mM NaCl, 5.9 mM KCl, 2.5 mM CaCl 2 , 1.2 mM MgCl 2 , 25 mM NaHCO 3 , 1.2 mM NaH 2 PO 4 , and 8 mM glucose), with the pH maintained at 7.4 by aeration with 95% O 2 , 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For intracellular recordings, the whole mount preparations were pinned in a 2.5-ml Sylgard-lined chamber and superfused continuously (2-3 ml/min) with a modified Krebs' solution containing 10 mM HEPES buffer at 30 -32°C (Hardwick et al, 1995;Braas et al, 1998;Tompkins et al, 2006Tompkins et al, , 2007. Cardiac ganglia were visualized with an inverted microscope equipped with Hoffman optics (Modulation Optics Inc., Greenvale, NY), and individual cardiac neurons were impaled using high-impedance borosilicate microelectrodes (2 M KCl-filled; 60 -100 M⍀).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is mediated by PAC1-R and cAMP production Tompkins and Parsons, 2008) and requires Ca 2ϩ influx (Tompkins et al, 2006). In contrast, the increased excitability of rat neonatal cardiac neurons induced by PACAP requires coactivation of PAC1-R and VPAC-R and release of Ca 2ϩ from intracellular stores (DeHaven and Cuevas, 2004).…”
Section: Pituitary Adenylate Cyclase-activating Polypeptidementioning
confidence: 99%
“…PACAP exhibits multiple regulatory actions on neurons (Arimura, 1998;Vaudry et al, 2000) and very potent effects on cardiac neuron excitability (Braas et al, 1998;Tompkins et al, 2006). We recently demonstrated that PACAP can be released from the preganglionic terminals during nerve stimulation (Tompkins et al, 2007).…”
Section: Atf-3 Induction In Cardiac Neuronsmentioning
confidence: 99%